DNA methylation of the oxytocin receptor gene predicts neural response to ambiguous social stimuli - Jack, Allison; Connelly, Jessica J.; Morris, James P. (Frontiers in Human Neuroscience, 2012)
Oxytocin and its receptor (OXTR) play an important role in a variety of social perceptual and affiliative processes. Individual variability in social information processing likely has a strong heritable component, and as such, many investigations have established an association between common genetic variants of OXTR and variability in the social phenotype. However, to date, these investigations have primarily focused only on changes in the sequence of DNA without considering the role of epigenetic factors. DNA methylation is an epigenetic mechanism by which cells control transcription through modification of chromatin structure. DNA methylation of OXTR decreases expression of the gene and high levels of methylation have been associated with autism spectrum disorders. This link between epigenetic variability and social phenotype allows for the possibility that social processes are under epigenetic control. We hypothesized that the level of DNA methylation of OXTR would predict individual variability in social perception. Using the brain’s sensitivity to displays of animacy as a neural endophenotype of social perception, we found significant associations between the degree of OXTR methylation and brain activity evoked by the perception of animacy. Our results suggest that consideration of DNA methylation may substantially improve our ability to explain individual differences in imaging genetic association studies.